El Control Tributario como Herramienta Clave para Contrarrestar la Evasión del Impuesto a la Renta de las Empresas. - Sanandrés Villacís, Joselin Alejandra (2022)
The Ecuadorian Tax Administration uses controls, the purpose of which is to verify that taxpayers comply with their tax obligations, through the application of these measures, it is possible to increase the collection of taxes in accordance with tax policies. The present work aims to analyze tax control as a key tool to counteract tax evasion; For this, the quantitative-qualitative methodology is applied, based on the description of facts, situations, data, attitudes, beliefs, and emotions of human talent, either individually or collectively, in order to analyze and understand them; In addition, it is considered to be descriptive and documentary, by registering the information, it was possible to analyze and interpret the behavior from the income tax evasion, in parallel a multiple case study was carried out, where several cases are used at the same time to study and describe reality. The TA exercises controls that make it possible to avoid deviations related to shell companies such as issuance of illegal invoices, control unusual movements or operations, carry out physical reviews of the supporting documentation, however, in what is analyzed in the cases it is observed that the taxpayer incurs in omissions, which may harm the State by preventing activities or social works from being carried out, the main reason for collecting taxes, this causes it not to declare in its entirety the values of the Income Tax, through the review of the rulings issued by the contentious tax court, made for income tax for the fiscal year. The Tax Administration has been directed with a coercive approach, but both theory and numerous studies have shown that it is important to consider the taxpayer's perception of the fairness of the tax system, as well as its morality